(untitled) (Medical Forum Monthly, 2022)
Objective: To correlate vitamin D levels with serum renin levels in hypertensive male subjects. Study Design: Analytical case control study Place and Duration of Study: This study was conducted at the Lahore General Hospital, Lahore from January to June 2015. Materials and Methods: The participants in this study were 75 male individuals were separated into stage I and stage II hypertension groups, with healthy attendants serving as controls. Subjects' blood pressure was recorded with a mercury sphygmomanometer, and blood samples were obtained for examination of vitamin D and renin levels. Results: Subjects included had a mean age of 39.97 ± 8.24 years. Mean vitamin D levels (ng/mL) were 35.99 ± 8.08, 28.71 ± 10.85 and 28.12 ± 9.94 in controls, stage I hypertension and stage II hypertension groups respectively. The association between serum vitamin D and renin levels among the three groups was statistically significant with an ‘r’ value of -0.275 and p value of 0.017 as indicated in Table.1 and Fig.1. Conclusion: Our findings in hypertensive patients showed an inverse relationship between blood pressure and vitamin D with an increase in levels of systolic BP, diastolic BP and plasma renin.